Urticated plaques in a child. (1st September 2022) - Tierney, Emma; Lynch, Maeve
Abstract: We present a case of an acute urticated eruption in a child, associated with acral oedema in the setting of recent infection and antibiotic therapy. There are a limited number of differential diagnoses, which we discuss in this article, while also highlighting distinguishing features and management considerations.